Necrotic Ulcers from Occlusive Vasculopathy Associated with Monoclonal B Cell Lymphocytosis - Delwyn Zhi Jie Lim; Shang-Ian Tee; Ling Cao; Ding Yuan Wang (Medical Journals Sweden, 2023)
Abstract is missing (Shot communication)